Effects of board gender and foreign directorship on the financial sustainability of Saudi listed firms: Does family ownership matter? - Mohammed Naif Alshareef; Hamid Ghazi H Sulimany (Heliyon)
This study investigates how family ownership may influence the effects of board gender and foreign directorship on the financial sustainability. The panel data of 103 Saudi non-financial listed companies from 2013 to 2022 was analyzed using fixed effects, and the generalized method of moments (GMM) was used for robustness test. The research findings suggest a strong and positive effect of foreign directorship on financial sustainability, consistent with the resource dependency view and agency theory. However, board gender exerts a negative and significant influence, contradicting existing theories. Further, the moderation results show that family ownership positively moderates the effects of both board gender and foreign directorship on financial sustainability. This positive moderating result supports the agency theory's argument that robust and stringent monitoring of corporate ownership may complement boards' functions and boost organizational efficiency. The policy decision of the findings is that setting corporate boards with a considerable ratio of foreign directors may lead to sustainable performance. Also, it implies that family ownership seems to be an essential mechanism that can neutralize the adverse effects of boardroom diversity on outcomes.